Comparison of patency of single and sequential radial artery grafting in coronary artery bypass. (23rd October 2021) - Kasahara, Hirofumi; Shin, Hankei; Takahashi, Tatsuo; Murata, Satoru; Mori, Mitsuharu
Abstract: OBJECTIVES: Sequential radial artery (RA) grafting has the potential to enhance arterial revascularization compared to single grafting. Sequential RA grafting was performed predominantly with a single side-to-side anastomosis. The study aimed to assess if sequential RA grafting improved long-term graft patency compared to single RA grafting. In addition, the anastomotic patencies of side-to-side and end-to-side anastomoses in sequential RA grafting were assessed. METHODS: Two hundred nineteen patients underwent isolated coronary artery bypass grafting with skeletonized RA conduits between 2005 and 2016. Of these, 208 patients underwent radiological graft assessment; thus, 125 and 83 patients underwent single and sequential RA grafting, respectively. The graft and anastomotic patency rates were estimated using the Kaplan–Meier method. RESULTS: The median follow-up period was 9.1 years, and the radiological assessment lasted 5.1 years. The overall RA graft patency rates at 1, 5 and 10 years were 99.4%, 92.7% and 88.1%, respectively. The RA graft patency rate for sequential grafting was similar to that for single grafting (88.7% vs 87.4% at 10 years; P  = 0.88). In the stratified analysis of anastomotic patency, the patency rate of side-to-side anastomoses of sequential RA grafting was significantly better than that of end-to-side anastomoses (100% vs 88.7% at 10 years; P  = 0.01). CONCLUSIONS: The long-term RA graft patencies of sequential and single grafting were equally high. The anastomotic patency of side-to-side anastomoses of sequential RA grafting was remarkably high. Considering these findings, the RA can be effectively used for multiple arterial coronary revascularizations. Abstract : Coronary artery bypass grafting (CABG) is a major procedure for improving survival in patients with obstructive coronary artery disease.